DOMESTIC BUSINESS EVENT TOURISM MARKETING STRATEGY - Desharyanto, Aditya Putra; Wulandari, Retno (UI Scholars Hub, 2021)
This paper discusses the application of the 6P marketing mix (Product, Price, Place/Distribution, Promotion, Politics, and Public Opinion) by Jakarta Tourism and Creative Economy Office through The Office of Tourism and Creative Economy in order to organize domestic MICE activities ( Meeting, Incentive, Convention, and Exhibition) in 2019 until 2020. This research uses the type of qualitative research and descriptive research with data collection techniques of observation, interviews, and literature studies. The results of the study are suggested and recommended to The Jakarta Tourism and Creative Economy Office to open new jobs, actively holding MICE events, especially business to customers (B2C), and establish cooperation with stakeholders by providing legal certainty.